HUBUNGAN PEMAHAMAN KONSEP ADAB SOPAN SANTUN DENGAN PERUBAHAN SIKAP SISWA - Yuli Kurnia; Adelina Hasyim; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2014)
This research aims to explain the correlation of courtesy norm concept comprehension with alteration of students attitudes in SMP Negeri 2 Waylima year 2013. This research uses descriptive quantitative method. Test, attitude scale and observation sheet are used as data collecting instrument. To analyze data uses interval and chi squared. This research population are 150 students and the sample are 38 students. The result of this research shows 50% students understand with the concept of courtesy norm, but 71,1% students tend to resist being polite. From the calculation using Chi Square formula obtained results X ² = 71.1, the contingency coefficient C = 0.80 and Cmaks = 0,81 and lies in the closeness of 0.56 to 0.83 (high category), so that the results of this research shows there is a correlation of understanding the concept of civilized manners with alteration of student attitudes in SMP Negeri 2 Waylima Year 2013.Tujuan penelitian ini untuk menjelaskan hubungan pemahaman konsep adab sopan santun dengan perubahan sikap siswa di lingkungan SMP Negeri 2 Waylima tahun 2013. Penelitian ini menggunakan metode deskriptif kuantitatif. Instrumen pengumpul data menggunakan tes, skala sikap dan observasi. Analisis data menggunakan Interval dan Chi Kuadrat. Populasi penelitian ini berjumlah 150 siswa, sampelnya berjumlah 38 siswa. Hasil penelitian menunjukan 50% siswa paham dengan konsep adab sopan santun, namun 71,1% cenderung menolak bersikap sopan santun. Dari hasil perhitungan yang menggunakan rumus Chi Kuarat diperoleh hasil X² = 71,1 dengan koefisien kontingensi C= 0,80 dan Cmaks = 0,81 dan terletak pada keeratan 0,56-0,83 (kategori tinggi) sehingga dari hasil pengujian tersebut diketahui bahwa ada hubungan pemahaman konsep adab sopan santun dengan perubahan sikap siswa di lingkungan SMP Negeri 2 Waylima Tahun 2013.Kata kunci: adab sopan santun, pemahaman konsep, perubahan sikap